Childhood obesity in relation to risk of dental caries: a cumulative and dose-response systematic review and meta-analysis - Mohammad Reza Bakhoda; Mohammad Mehdi Haghighat Lari; Gholamreza Khosravi; Zeinab Khademi; Fatemeh Abbasi; Alireza Milajerdi (BMC, 2024)
Abstract Introduction Earlier studies reported inconsistent findings for the association of childhood obesity with the risk of dental caries. In this systematic review and meta-analysis, we aimed to summarize earlier studies on the association of overweight and obesity with risk of dental caries in children. Methods Relevant studies published up to December 2023 were identified through searches in PubMed, MEDLINE, SCOPUS, EMBASE, and Google Scholar, using suitable keywords. All observational studies, including cross-sectional or cohort or case-control studies, about the association of each obesity index with risk of dental caries in children which reported odds ratio (OR), hazard ratio (HR), or relative risk (RR) and 95% CIs, were included. Studies involving adults, randomized clinical trials, studies on animals or pregnant women, and studies on other dental disorders were excluded. Risk of bias was assessed using standard methods for observational studies. A total of 22 studies including 40673 participants were included. Studies were pooled using the random-effect model, and results were synthesized with subgroup analyses and assessments of heterogeneity. Limitations included potential publication bias and heterogeneity among study designs. The quality of the included studies was assessed using the Newcastle-Ottawa scale (NOS). Results Children at the highest category of BMI were 44% more likely to have early childhood caries (ECC) than those at the bottom (OR: 1.44; 95% CI: 1.16 to 1.78). Moreover, combined analysis also showed no significant association between waist circumference (WC) and risk of dental caries in children. However, significant linear and non-linear associations were found between BMI and risk of childhood dental caries. No publication bias was found for the relationship between BMI and the risk of ECC based on visual inspection of a funnel plot and Egger's test. Conclusions This study showed a significant direct association between BMI and the risk of dental caries in children. Non-linear analysis showed higher risk of dental caries in children with higher BMI and also among underweight children. Further prospective studies are required to expand current knowledge in this issue. Impact statement The findings of this study have significant implications for public health and dental care, suggesting association between BMI and the risk of dental caries in children. This comprehensive meta-analysis is among the first to summarize earlier publications on the association of obesity with risk of dental caries in children, highlighting the need for more accurate methods of obesity assessment and further research to understand this relationship better. These findings can help inform public health policies and interventions to reduce the prevalence of childhood obesity and dental caries.